2023
DOI: 10.5465/amj.2020.1054
|View full text |Cite
|
Sign up to set email alerts
|

Creative Jolts: Exploring How Entrepreneurs Let Go of Ideas During Creative Revision

Abstract: Acknowledgements:We are grateful for extremely valuable advice and feedback from Associate Editor Andrew Nelson and three anonymous reviewers. We would also like to thank Jennifer Mueller and Poornika Ananth for insightful comments on earlier drafts of this paper; the entrepreneurs and co-working space leaders who dedicated hours of time and provided support to our research; and the ESRC for making the project possible (ESRC Grant ES/N007301/1). Finally, we are grateful to Julia Oertli who worked as a research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…Then, problem/solution combinations that were not previously formulated emerge by surprise (Von Hippel and von Krogh, 2016). Thus, serendipitous innovation can be differentiated from targeted innovation by its element of surprise , and unplanned, exploratory learning outcomes often emerge from experimentation (Garud et al, 2018; Smith and Hibolling, 2022; Toivonen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Then, problem/solution combinations that were not previously formulated emerge by surprise (Von Hippel and von Krogh, 2016). Thus, serendipitous innovation can be differentiated from targeted innovation by its element of surprise , and unplanned, exploratory learning outcomes often emerge from experimentation (Garud et al, 2018; Smith and Hibolling, 2022; Toivonen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes creators generate all their ideas before evaluating them, but at other times they may evaluate a small set of ideas and build on them (Harvey and Kou, 2013; Harrison and Rouse, 2015). Creators may iterate between these processes repeatedly over the course of a long-term creative project (Harvey, 2014; Amabile and Pratt, 2016), sometimes returning to square one to make significant changes to a well-developed idea (e.g., Rahman and Barley, 2017; Toivonen et al, 2022).…”
Section: Managing Ideas In Creative Workmentioning
confidence: 99%
“…The view that creative portfolios continually evolve also has implications for research on creative identities. Prior research has shown how creators can come to see ideas as extensions of the self (Elsbach, 2009;Grimes, 2018) and experience negative emotions and identity threat when they face the prospect of changing or letting go of those ideas (Rouse, 2013;Toivonen et al, 2022). In the context of a creative portfolio, a creator may derive a sense of identity from the portfolio of projects they have worked on rather than from a single idea that they become attached to.…”
Section: Contributions Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in the later stages of the innovation process, people engage in creative activities to envision solutions, a process that involves first imagining ideas and concepts, then evaluating whether they are appropriate in the new context (Perry-Smith & Mannucci, 2017). This activity may require them to shift, transform or let go of ideas and beliefs in favour of new ones (Toivonen et al, 2023), experiencing a meaning void to be filled through social interactions and sensemaking (Kaffka et al, 2013). Thus, sensemaking is also required in the final stages of developing plausible and sustainable outcomes in a new environment (Pendleton-Jullian & Brown, 2016).…”
Section: Introductionmentioning
confidence: 99%